BIOAKTIFITAS ANTIINFLAMASI EKTRAK METANOL RIMPANG SIJANGKANG (Hornstedtia scyphifera var. Fusiformis Holttum) TERHADAP TIKUS PUTIH JANTAN - Mevy Trisna; Renatalia Fika; Ilza Fitri Handayani; Ainun Naim; Muhajri Agusfina (Journal Pharma Saintika, 2025)
An investigation examined the anti-inflammatory effects of the methanol extract from the Sijangkang rhizome (Hornstedtia scyphifera var. Fusiformis Holttum) on male albino rats that were induced with 1% carrageenan at a volume of 0.2 ml/rat. The tool used in this test is a Plethysmometer with a working principle using Archimedes' law. A Plethysmometer is a tool used to measure edema volume. The way it works is based on measuring the volume of fluid due to the immersion of the organ whose degree of inflammation is measured into mercury liquid. The working principle is that if an object is dipped into a liquid, the object will get an upward pressure equal to the liquid that is pushed by the object. From the results of the research that has been done, it can be concluded that the methanol extract of sijangkang rhizome has anti-inflammatory activity. The research conducted is an experimental study using 12 test animals consisting of 4 treatment groups, namely 1 negative control group (aquadest), and 3 groups of test substances methanol extract of sijangkang rhizome. The doses used were 2 mg/200 g BW/5 ml, 4 mg/200 g BW/5 ml, and 8 mg/g BW/5 ml. The negative control group and the test group with doses of 4 mg/200 g BW and 2 mg/200 g BW showed a very high and continuously increasing percentage of edema formation. This was due to the fact that the negative control group received only distilled water, while the test group was administered a small amount of the test substance that failed to prevent edema formation. In contrast, the test substance, at a dose of 8 mg/200 g body weight/5 ml, exhibited anti-inflammatory properties.